Workforce—The Bedrock of Aged Care Reform. (9th June 2021) - Bonner, Rob; Peters, Micah D. J.; Butler, Annie
Abstract: The Australian Royal Commission into Aged Care Quality and Safety made 148 recommendations to reform Australian aged care. The recommendations concerning the sector's workforce are integral to ensuring that the widespread neglect and failures characterising the sector be addressed and prevented. This paper discusses several of the Commission's recommendations in relation to issues that we see as foundational for ensuring sustained success of urgent sector‐wide reform. We focus on mandated staffing levels and skills mix, attraction and retention, education and training, staff registration, and funding transparency and accountability.